Predicting mechanical properties of enhanced performance concrete using compressive strength - Camões, Aires (2004)
Mechanical properties of concrete are usually evaluated from compressive strength test results. Extensive literature, codes and regulations recommend the prediction of mechanical properties such as splitting and flexural tensile strength using the compressive strength of cylindrical specimens. These expressions are not related with the type of concrete and, generally, are only a function of the cylindrical compressive strength. It is the objective of this research work to investigate the validity of the existing relationships for enhanced performance concrete, obtained by replacing cement with fly ash for up to 60% in weight. The experimental program investigated the effect of replacing cement with fly ash on the mechanical properties, i.e. compressive strength, splitting-tensile strength and flexural-tensile behaviour. Results obtained show that, in most cases, a good linear correlation exists between the evaluated mechanical properties, i.e. splitting-tensile strength, flexural-tensile strength and elasticity modulus in flexure, and the square root of compressive strength. This further indicates that an increase in the compressive strength produces a less pronounced increase of the tensile strength.